Role of Salivary Tumor Necrosis Factor-alpha and Immunoglobulin- A in Recurrent Aphthous Stomatitis - Al-Ghurabei, Batool H (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Until today, the etiology of recurrent aphthous stomatitis (RAS) remains unknown, although hints of its etiologic basis lay on genetic susceptibility, infectious agents and alterations in immune mechanics. Objectives: The aim of this study was to investigate the possible alterations in salivary tumor necrosis factor-alpha (TNF-α) and Immunoglobulin-A (IgA) level in patients with RAS and its relation with clinical types of disease. Subjects and Methods: Salivary TNF-α levels were investigated in 50 RAS patients and 25 healthy controls by enzyme-linked immunosorbent assay (ELISA). Single radial immune diffusion method was used for estimation of IgA level in two studied groups. Results: Salivary level of TNF-α was significantly higher in RAS patients than in healthy controls (p<0.001), Moreover, the level of TNF-α was significantly increased in minor type of disease than in major and herptiform types (p<0.05). On the other hand, the level of IgA showed no significant differences between patients and healthy controls and neither among clinical types of disease (p>0.05). Conclusion: These findings suggest that saliva provides an ideal medium for the detection of proinflammatory markers of the oral cavity, moreover; salivary TNF-α may play an important role in pathogenesis of this disease and it may also have an important role in the search of new treatments for this disease. As well as these results indicated to a possible role of mucosal immune system in pathogenesis of RAS.